Infographics or video; which one is more effective in asthmatic patients' health? a randomized clinical trial. (2nd December 2019) - Ebrahimabadi, Maryam; Rezaei, Korosh; Moini, Abdollatif; Fournier, Andrew; Abedi, Ahmadreza
Abstract: Objective: Asthma disease is a complex medical condition for which the control of symptoms depends on sufficient patient knowledge, self-care, and adherence to medication protocols. Researchers conducted this study to evaluate the impact of infographics and video on asthma patients' adherence to medication. Methods: A randomized clinical trial in which 80 asthmatics were enrolled and allocated to two study groups (infographic and video groups). Researchers used questionnaires to gather demographic data. A nurse assessed Morisky adherence to medication. Researchers performed data analysis using repeated measurements and Least Significant Difference (LSD) in SPSS software version 23. Results: There was no significant difference between the two study tracks ( P  > 0.05) in the demographic data and adherence to medication in the pretest. The differences between the two intervention groups throughout the one-month follow-up were statistically significant ( P  < 0.05). There were significant differences between the two intervention groups in pretest and post-test, and pretest and follow-up ( P  < 0.05). However, there were no significant differences between the two intervention groups in post-test and follow-up ( P  > 0.05). Conclusions: According to the study findings, both the infographic and video formats may have led to an increase in adherence to medication protocols among asthma patients; but it seems that the infographic format is preferred for long- term use because it does not require usage of a facility. However, education format of asthmatic people is dependent on conditions and patient preferences.